Presuppositions of Social Activism in Marcus Rashford’s Open Letter - Alya Zasha Khalisa; Widyastuti Widyastuti (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2022)
This study analyzed the presuppositions in Marcus Rashford's open letter to the UK government regarding free school meals for children all over UK during the outbreak of Covid-19. His open letter is an essential part of social activism in a changing society. It was written with enthusiasm, optimism, and positivity for a new future. The study is conducted to fill the gap between the previous studies since no research has analyzed an open letter before. This study used Yule's theory (1996) of presuppositions and Cutting (2002) to analyze the data found in the letter. The results of the study found that the open letter used four kinds of presuppositions, which is existential, factive, lexical, and counterfactual presuppositions. Rashford was able to provide the audience with new data as an addition to the material they already knew by utilizing those presuppositions. Additionally, it refutes a common misconception. In this case, the UK government's stance is successfully influenced.